Magnetic solid‐phase extraction method for extraction of some pesticides in vegetable and fruit juices. Issue 8 (19th February 2020) - Farajzadeh, Mir Ali; Safi, Razieh; Yadeghari, Adeleh
Abstract: A new version of magnetic solid‐phase extraction performed in a narrow‐bore tube has been proposed for the extraction and preconcentration of different pesticides from various vegetable and fruit juices followed by gas chromatography. A few milligrams of C8 @SiO2 @Fe3 O4 nanoparticles are added into an aqueous sample solution placed in a narrow‐bore tube. The sorbent particles move down through the tube under gravity and are collected at the end of the tube by applying an external magnetic field. The end of the tube is narrower and it is connected to a stopcock. After a predetermined time, the stopcock is opened and the solution is passed through the bed of the sorbent maintained by the magnet. Then the adsorbed analytes are desorbed using an elution solvent. To achieve high enrichment factors, a dispersive liquid–liquid microextraction method is carried out. The nanoparticles were characterized by scanning electron microscopy, X‐ray diffraction, and FTIR spectroscopy. Under the optimum extraction conditions, limits of detection and quantification were in the ranges of 0.1–0.3 and 0.3–0.9 μg/L, respectively. High enrichment factors (1166–1605) and good extraction recoveries (58–80%) were obtained.